1995
DOI: 10.1161/01.hyp.25.6.1144
|View full text |Cite
|
Sign up to set email alerts
|

Low Urinary Sodium Is Associated With Greater Risk of Myocardial Infarction Among Treated Hypertensive Men

Abstract: A sodium-reduced diet is frequently recommended for hypertensive individuals. To determine the relationship of sodium intake to subsequent cardiovascular disease, we assessed the experience of participants in a worksite-based cohort of hypertensive subjects. The 24-hour urinary excretion of sodium (UNaV), potassium, creatinine, and plasma renin activity was measured in 2937 mildly and moderately hypertensive subjects who were unmedicated for at least 3-4 weeks. Morbidity and mortality in these systematically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
188
2
9

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(204 citation statements)
references
References 39 publications
5
188
2
9
Order By: Relevance
“…This did not prevent Alderman and colleagues drawing attention to the similarity of their conclusions to those they had come to in their previous paper. They commented that: 'The inverse association of salt intake with mortality is consistent with the findings of a similar observational study 7 of 3000 participants in a systematic programme to control hypertension'. In other words in spite of the misrepresentations and faulty urinary sodium excretion estimations in their first paper, and the defective data in their second, Alderman and colleagues wished it to be known that they still subscribe to the myth that a low salt intake is dangerous.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This did not prevent Alderman and colleagues drawing attention to the similarity of their conclusions to those they had come to in their previous paper. They commented that: 'The inverse association of salt intake with mortality is consistent with the findings of a similar observational study 7 of 3000 participants in a systematic programme to control hypertension'. In other words in spite of the misrepresentations and faulty urinary sodium excretion estimations in their first paper, and the defective data in their second, Alderman and colleagues wished it to be known that they still subscribe to the myth that a low salt intake is dangerous.…”
supporting
confidence: 55%
“…In the past 3 years Alderman and colleagues have published two papers which they believe to show that an habitual reduction in salt intake in humans increases the risk of myocardial infarction. 7,8 I believe that this assertion is not supported by the published evidence. The first paper claimed that among a group of 3000 patients with hypertension, 'baseline' 24 h urinary sodium excretion was inversely related to subsequent myocardial infarction and cardiovascular disease and that therefore the habitual consumption of a low salt intake increases the incidence of myocardial infarction'.…”
mentioning
confidence: 87%
“…Alderman et al have attempted to look at the effect of salt intake on cardiovascular disease in two cohort studies, one is a follow-up study of a worksite screening project in New York, 46 and the other involved the NHANES 1Fa dietary survey of US adults from the mid 1970s. 47 They suggested that a low salt diet might increase the risk of cardiovascular disease.…”
Section: Mortality Studiesmentioning
confidence: 99%
“…2 Since epidemiology is about associations, alternate explanations for the observed facts must always be explored. The scenario Professor de Wardener proposed must be tested for compatibility with the information in the original published article.…”
mentioning
confidence: 99%
“…The relevant published data, to our knowledge, is limited to three prospective observational studies. 2,4,5 They provide no evidence that a low sodium intake is beneficial, nor that a high sodium intake is harmful. Indeed, two of these three studies raise concerns about the safety of a low sodium intake.…”
mentioning
confidence: 99%